NUCB2/Nesfatin-1 Regulation of Chronic Visceral Hyperalgesia - Qiaoyan Gu; Yuan Lei; Jianming Wu; Ting He; Juanjuan Li; Shanshan Song (Applied Bionics and Biomechanics)
Objective. We previously described that different concentration Nucleobindin-2 (NUCB2)/Nesfatin-1 gradients differently regulated visceral hypersensitivity in irritable bowel syndrome. Therefore, this study is aimed at evaluating the effect of NUCB2/Nesfatin-1 on model rats with chronic visceral hyperalgesia. Methods. Neonatal and mature Sprague-Dawley rats were randomly divided into the healthy control and chronic visceral hyperalgesia model groups. The model was built by combining maternal separation with the acetic acid enema. The models were identified by the distension volume threshold to reach abdominal withdraw reflex AWR score=3, histological staining, and myeloperoxidase (MPO) detection. The visceral sensitivity to chronic visceral hyperalgesia was then evaluated. Result. Rats in the model group responded more strongly to pulling stimulation than healthy controls; the distension volume threshold causing AWR3 response in model rats was lower than the control group before NUCB2/Nesfatin-1 intervention. After intervention, the distension volume threshold was significantly lower in the NUCB2/Nesfatin-1 central intervention group than in the NUCB2/Nesfatin-1 peripheral intervention group, and the peak value of external oblique muscle electrical activity was significantly higher. Additionally, compared with the male intervention group, in the female intervention group, the volume threshold was significantly lower and the peak value was higher. Conclusion. NUCB2/Nesfatin-1 could regulate visceral sensitivity in chronic visceral hyperalgesia model rats; its regulatory effect correlated with the type of NUCB2/Nesfatin-1 intervention approaches (central or peripheral) and sex (male or female).